Tree Species Composition of the Lowland Forest in Bukit Baka Bukit Raya National Park, East Kalimantan, Indonesia - Ruliyana Susanti; Deden Girmansyah; Bayu Arif Pratama; Supardi Jakalelana (Reinwardtia, 2026)
SUSANTI, R., GIRMANSYAH, D., PRATAMA, B. A. & JAKALELANA, S. 2026. Tree species composition of the lowland forest in Bukit Baka Bukit Raya National Park, East Kalimantan, Indonesia. Reinwardtia 25(1): 31‒40. — Tree species diversity and structural characteristics in the lowland forest of Bukit Baka Bukit Raya National Park (TNBBBR) were examined to assess the overall floristic diversity of this conservation area. A survey was conducted at the national park boundary with PT. Sari Bumi Kusuma, a forest company concession in East Kalimantan. Data were collected using transect plots of 50 × 10 m at 100 m elevation intervals across three locations (Km. 37, Km. 39a, and Km. 39b), for a total of eight plots. All trees with a diameter at breast height (DBH) ≥ 10 cm were measured and identified. We recorded 352 trees inside the plots, representing 138 species and 35 families, with a total basal area of 24.7 m2/0.4ha. The dominant families in terms of basal area are Dipterocarpaceae and Myrtaceae. We found 79 Dipterocarpaceae trees, representing 22.4% of individuals, in the surveyed area. In terms of species richness, Dipterocarpaceae composed 21% of the species. There were seven genera (Dipterocarpus, Dryobalanops, Hopea, Shorea, Rubroshorea, Richetia, and Anthoshorea) and 29 species. Shorea was the richest genus among them. Shorea laevis, Rubroshorea leprosula, and R. dasyphylla were the most common species found in Dipterocarpaceae.